The effect of the Affordable Care Act on Medicaid payments in long-term care facilities. (2nd January 2022) - Walker, Victoria; Ruley, Morgan; Nelson, Laikyn; Layton, Whitney; Coustasse, Alberto
ABSTRACT: Long-term care has been defined as a continuation of medical services, social services, and housing for patients with chronic health conditions, which have limited their abilities to partake in everyday activities. In the United States, the Affordable Care Act (ACA) was enacted to expand coverage for Medicaid and to improve the quality and cost of healthcare. The purpose of this study was to evaluate the impact of the ACA on long-term care to determine if it has increased Medicaid payments. The methodology for this investigation utilized a literature review following a systematic approach utilizing 48 references and complemented with a semi-structured interview. It was found that the ACA has increased Medicaid payments, and the number of uninsured patients has decreased. With the implementation of the ACA, nursing homes and lifelong care facilities have been required through the ACA to meet new requirements that have made it easier to file complaints about the quality of care. This study also suggested a decrease in readmission rates with Medicaid and the ACA in long-term settings. The ACA implementation has increased Medicaid payments, and quality of care has been improved through a decrease of readmissions, ulcers, and falls in long-term care facilities.